Forest School practice in Canada: a survey study - Boileau, Elizabeth Y. S.; Dabaja, Ziad F. (Journal of Outdoor and Environmental Education, 2020)
Over the last decade, interest in nature-based educational programs has been growing in Canada, yet there has been little research on the nature of these programs and how they are being implemented. This small-scale study provides baseline information on the characteristics of Canadian Forest Schools, the challenges that educators face in starting up these outdoor programs, and the potential benefits for enrolled children. An online survey study was conducted in the fall of 2017, to which 25 Forest School educators from across Canada responded. Results suggest that Canadian Forest School programs vary in terms of size, age of the children, type of outdoor setting, funding source, and schedule. Participants reported facing challenges such as finding an appropriate outdoor site, safety concerns related to outdoor activities, and the lack of support from different stakeholders. Many of these barriers were surmounted by developing relationships with local partners, adapting programs to comply with local regulations, and educating the community on Forest School pedagogy. In line with the growing international body of research on the benefits of Forest School (e.g., Elliott & Chancellor, 2014; Müller et al., 2017; Murray & O’Brien, 2005; Slade, Lowery & Bland, 2013), Canadian Forest School educators have observed benefits for the children, including the development of their social and physical skills and self-confidence, increased appreciation for nature, and enhanced creativity. Further research is needed to fully capture and examine this growing practice in the Canadian context.